Targeting and activation of macrophages in leishmaniasis. A focus on iron oxide nanoparticles - Palomino-Cano, Carmen; Moreno, Esther; Irache, Juan M.; Espuelas, Socorro (Frontiers in Immunology, 2024)
Macrophages play a pivotal role as host cells for Leishmania parasites, displaying a notable functional adaptability ranging from the proinflammatory, leishmanicidal M1 phenotype to the anti-inflammatory, parasite-permissive M2 phenotype. While macrophages can potentially eradicate amastigotes through appropriate activation, Leishmania employs diverse strategies to thwart this activation and redirect macrophages toward an M2 phenotype, facilitating its survival and replication. Additionally, a competition for iron between the two entities exits, as iron is vital for both and is also implicated in macrophage defensive oxidative mechanisms and modulation of their phenotype. This review explores the intricate interplay between macrophages, Leishmania, and iron. We focus the attention on the potential of iron oxide nanoparticles (IONPs) as a sort of immunotherapy to treat some leishmaniasis forms by reprogramming Leishmania-permissive M2 macrophages into antimicrobial M1 macrophages. Through the specific targeting of iron in macrophages, the use of IONPs emerges as a promising strategy to finely tune the parasite-host interaction, endowing macrophages with an augmented antimicrobial arsenal capable of efficiently eliminating these intrusive microbes.